W3C web accessibility initiative under the microscope : Identifying assumptions of users and their involvement in digital accessibility design - Karasjärvi, Pia; Mäkipää, Juho-Pekka; Rousi, Rebekah (Design Research Society, 2024)
In addition to the well-known Web Content Accessibility Guidelines, Web Accessibility Initiatives (WAI) also provide additional information and best practices for web practitioners on involving users with disabilities in their projects. Given the central role that the WAI possesses in the case of web accessibility, how they perceive and what they say about user involvement is regarded as significant. This paper examines how users with disabilities are represented, and more importantly, how they are treated in the recommendations. Critical close reading was performed on text produced by WAI regarding user involvement of people with disabilities. We found a reduction in the nature of how people with disabilities are established as human equals in the design process. Based on our analysis we identified nine themes underlying the view of users with disabilities and their involvement. The themes illuminate ethical issues and hidden assumptions that need close attention in the future.
Keywords: disability justice; design justice; digital accessibility; user involvement; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Viestintätieteet|en=Communication Studies|